Association Between Maternal Characteristics and the Incidence of Severe Preeclampsia Among Pregnant Women: A Literature Review - Karningsih Karningsih; Liliek Pratiwi; Harnanik Nawangsari; Mardeyanti Mardeyanti; Rosni Lubis (Indonesian Journal of Global Health Research, 2026)
Severe preeclampsia remains a leading cause of maternal and perinatal morbidity worldwide. Identifying specific maternal characteristics is crucial for early intervention. This review synthesizes evidence regarding the association between maternal traits and severe preeclampsia incidence. A systematic literature search was conducted across PubMed, Google Scholar, and ScienceDirect for studies published between 2016 and 2025. Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) checklist, five high-quality articles were selected based on strict eligibility criteria. Synthesis of the five core studies identifies advanced maternal age (>35 years), high pre-pregnancy Body Mass Index (BMI), chronic hypertension, parity, and inadequate antenatal care (ANC) as primary predictors. These factors significantly elevate the risk of progression to severe clinical features. Early screening of maternal risk profiles and optimized antenatal monitoring are essential to mitigate the incidence of severe preeclampsia.